A cross-national comparison of public project benefits management practices – the effectiveness of benefits management frameworks in application. Issue 8 (10th June 2020) - Williams, Terry; Vo, Hang; Bourne, Mike; Bourne, Pippa; Cooke-Davies, Terry; Kirkham, Richard; Masterton, Gordon; Quattrone, Paolo; Valette, Jason
Abstract: Benefits are the principal reason why an organization may seek to enact change through programmes and projects. The discipline of identification, definition, planning, tracking and realization of benefits is recognized to be instrumental in achieving organizational strategy. In this study, we describe the results of a cross-national comparison of public sector benefits management (BM) practices in Australia, Canada, the UK and the USA. It explores 'BM practices in action', considering to what extent 'espoused' or 'mandated' frameworks are actually practised and perceived by their users. Employing qualitative analysis, semi-structured interview data were analysed from 46 participants with experience in sponsoring, managing and/or reviewing government projects. The results expose considerable variation in the adoption and standardization of BM frameworks from inter and intragovernmental perspectives. We evidence a strong focus on benefits identification across the data set, specifically at the outset (the business case stage seeking project approval) and observe deterioration in focus as the project or programme progresses through the authorization (or assurance) approval gates towards close-out and operations. The results further emphasize the prominence of political interest, leadership buy-in, a benefits-driven culture and a transparent benefits reporting mechanism in the implementation of 'effective' BM frameworks.